Produção de biopolímero utilizando resina da ciriguela (Spondias purpurea) - Queiroz Junior, Antonio Batista de (Universidade Federal Rural do Semi-Árido, 2018)
Conventional synthetic polymers are produced from petroleum byproducts, a non-renewable natural resource, and cause various environmental problems stemming mainly from their difficult degradation that can take hundreds of years. Based on the principle of sustainability and seeking to minimize the environmental impacts caused by them, biopolymers are emerging new polymer models produced from renewable raw materials that use carbon from renewable sources such as corn, sugarcane, cellulose. In this sense, this study developed a biopolymer that has Ciriguela resin as its raw material. For the synthesis of the biopolymer blends were tested in proportions of 50%, 30% and 10% using commercial starch and natural starch extracted from the potato. Once the biopolymer was synthesized for its characterization, permeability, microscopy, combustion test and biodegradability analyzes were performed. The results demonstrate that the structural arrangement of Ciriguela biopolymer obtained from natural starch (BCAN) in the proportion 10% shows greater similarity to conventional polymeric films, the permeability test showed that the natural polymer product resists for a longer time the absorption of liquids and as for the combustion process, it was possible to visualize that the polymer burned completely and that it did not produce dark smoke and residues. Moreover, after one week the biopolymer of the natural starch citrate 10% (BCAN10) was totally decomposed in moist soil. In this perspective, the BCAN10 presented better conditions for the improvement of a polymer film model which can be used as an alternative for the industry instead of the polymers obtained from fossil sources.
Keywords: Amido Natural; Amido Comercial; Filme polimérico; Caracterização; Biodegradabilidade; Natural Starch; Commercial Starch; Polymeric film; Characterization; Biodegradability; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA